Chemical Constituents from Schefflera tribracteolata in Vietnam - Doan, Lan Phuong (Old Journal, 2018)
Ginsenoside Rgl, 3β, 6α, 12 β, 20S-tetrahydroxydammar-24-en 6-O-[β -D-glucopyranoside]; gypenoside XVII (3β,12β)-20-[(6-O-(β-D-glucopyranosyl)-β-D-glucopyranosyl)oxy]-12-hydroxydammar-24-en-3-yl β-D-glucopyranoside. These compounds were elucidated using a combination of UV, IR, 1D and 2D NMR techniques (1H-, 13C-NMR, COSY, HSQC and HMBC) and MS analyses.